Utilization of Information Technology in Increasing the Effectiveness of Citizenship Learning - Rachmanto, Teguh Basuki; Akande , Itunu Olaniran (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This study aims to explore the use of Information and Communication Technology in Citizenship Education learning at State Junior High School 5 Semarang and analyze its impact on student engagement and understanding of the concepts taught. Methodology: This study uses a qualitative method with data collection techniques through interviews with two teachers and five students. The data obtained were analyzed using a descriptive approach. Main Findings: The results of the study indicate that the use of information and communication technology in Citizenship Education learning helps improve interaction between teachers and students, makes learning more interesting, and makes it easier for students to understand abstract concepts. However, there are obstacles such as limited devices and unstable internet connections, which can interfere with the learning process. The novelty of this study lies in the holistic approach that not only assesses the effectiveness of information and communication technology in delivering material, but also considers how this technology can increase student active involvement in learning. Novelty/Originality of this study: These findings provide an important contribution to developing more interactive and technology-based citizenship learning strategies.